The Development Of Fast Charger 48V Lead Acid Battery For Electrical Scooter MAD 1000 & MAD 1300 Model - Mohd Ab. Halim, Mohd Firdaus; Abdullah, Abdul Rahim; Haji Azlan, Umar Al-Amani; Mohd Aras, Mohd Shahrieel; Mohd Annuar, Khalil Azha; Azahar, Arman Hadi; Attan, Hassan; Harun, Mohamad Haniff; Nawiah, Nedzarul; Md Som, Mohd Khairul Syazuan (UTeM, 2019)
Lead acid battery is a robust and widely used in small electric vehicle because of its price tag. It can be considered to be one of the mature battery in the market thus the charger too. Each lead acid battery from different manufacturer possess different characteristic hence not all charger is suitable for any lead acid battery. The experiment was conducted to determine the charging profile of a 12 V cells lead acid battery connected in series to make 48V battery source. The charging current and voltage were logged and analysed for 3 charge rate. The measurement design of experiment is presented in detail as well. The experiment was repeated for at least four times. As the charging rate increase, the time taken for the charging process to complete became shorter. Nevertheless, we saw that the full battery capacity reduced at faster rate for a higher charger rate. The charging profile of the battery are also validated by the single-cell 12V battery to prove the series and parallel charging significance.